2015
DOI: 10.1007/s00192-015-2798-2
|View full text |Cite
|
Sign up to set email alerts
|

Retropubic tension-free vaginal tape and inside-out transobturator tape: a long-term randomized trial

Abstract: In the long term, the proportion of patients with complications and the cure rates of the two procedures did not differ significantly. The long-term complication rates were high, but morbidity was low, and the QOL remained improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 30 publications
7
44
2
1
Order By: Relevance
“…Further sensitivity analyses limited to the 5 RCTs with follow-up durations >60 mo [21,34,[37][38][39] demonstrated similar outcomes for RP-TVT and TO-TVT in terms of objective cure rate, subjective cure rate, vaginal erosions, storage and voiding LUTS, and reoperation rates (see supplemental figure 1). …”
Section: Randomized Controlled Trials Comparing Retropubic With Transmentioning
confidence: 88%
See 1 more Smart Citation
“…Further sensitivity analyses limited to the 5 RCTs with follow-up durations >60 mo [21,34,[37][38][39] demonstrated similar outcomes for RP-TVT and TO-TVT in terms of objective cure rate, subjective cure rate, vaginal erosions, storage and voiding LUTS, and reoperation rates (see supplemental figure 1). …”
Section: Randomized Controlled Trials Comparing Retropubic With Transmentioning
confidence: 88%
“…Interestingly, Khan et al reported presence of scar pain also following autologous PVS, indicating that such risk is not limited to MUS [19]. Two recent studies reported 6.4% and 9% groin/inguinal pain/discomfort at 7 and 10-years follow-up respectively following TO-TVT [39,49]. Intractable suprapubic pain has been previously described following colposuspension and defined as post-colposuspension syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the studies in the literature did not present these outcomes. While Albo et al reported persisting pain for more than 6 weeks in 2.17% of their cohort at 2 years, Zhang et al reported significant pain in 9.16% at 5 years and Ross et al substantial pain in 18.78% at 5 years. Regarding sexual function, although the available literature suggests an overall postoperative improvement, de novo dyspareunia has been shown to affect 6.66% to 8.82% of women.…”
Section: Methodsmentioning
confidence: 94%
“…While the cure rates of the two procedures are similar, the insertion of TO‐MUS has been associated with a lower risk of bladder perforation and voiding dysfunction and a higher risk of groin pain and repeat continence surgery. Long‐term outcomes were reported by six RCTs of TO‐MUS vs RP‐MUS …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation